Cathodic stripping voltammetry of copper-complexed reactive dyes at a hanging mercury drop electrode : reactive violet 5 - Fogg, Arnold G.; Rahim, A.; Yusoff, H. M.; Ahmad, Rahmalan (Elsevier, 1997)
Reactive Violet 5 and its hydrolysis product, which is produced as a side product in the dyeing process, can be determined in an admixture at sub-ppb levels by cathodic stripping voltammetry because the potentials of their azo reduction peaks are separated sufficiently. For both dyes, at intermediate pH values the azo peak is preceded by a complexed -copper reduction peak at a less negative potential, which aids the identification of the dyes. The use of pH 6 EDTA buffer removes the complexed-copper peak, as does the use of an acidic buffer (pH < 3). This unusual use of EDTA as a pH buffer facilitates the determination of mixtures of the dye and its hydrolysis product.